Procesy urbanizacji wsi na obszarach metropolitalnych - Brol, Ryszard (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
This paper presents identification of dynamic of rural areas' urbanization within rural poviats: Wroclawski, Krakowski and Poznanski (they all are parts of metropolitan areas). The demographic and economic analysis allowed to confirm thesis (stated by the author in the middle of 1990s) that influence of economic and political transition and development paradigm would fasten urbanization of rural areas within metropolitan areas and next within other areas. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1143, s. 97-105